Модельер: роман / Рэчел Линдсей ; [перевод с англ. А. Г. Николенко] - Линдсей Рэчел (Цветы любви, 2002)
Экземпляры: Ф. 10 (20200625) / Инвентарный номер: 47888 / Цена: 37.00 / Сис.шифр: 84(4 Вел) / Авт.знак: Л 59 / ГРНТИ: 17.82 / ББК: 84(4 Вел)